2020
DOI: 10.1080/23802359.2020.1731356
|View full text |Cite
|
Sign up to set email alerts
|

Complete mitochondrial genome of the Ruff, Calidris pugnax(Aves, Scolopacidae)

Abstract: This paper reports the mitochondrial genome of Calidris pugnax, which is a closed circular molecule of 16,902 bp. The overall base composition of this species is 25.2% T, 30.6% C, 32.0% A, and 12.2% G, with an A þ T content of 55.2%. The structure of the mitogenome is a typical vertebrate mitochondrial gene arrangement. Phylogenetic analysis of complete mitochondrial genome concatenated sequences from 13 species from 6 genera was conducted using the maximum-likelihood (ML) model. The topology demonstrated that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
(5 reference statements)
0
3
0
Order By: Relevance
“… 2020 ), Calidris pugnax MN956840 (Chen et al. 2020 ), Calidris pygmeus KY434065 (Joen et al. 2017 ), Calidris ruficollis MG736926 (Chen et al.…”
Section: Methodsmentioning
confidence: 99%
“… 2020 ), Calidris pugnax MN956840 (Chen et al. 2020 ), Calidris pygmeus KY434065 (Joen et al. 2017 ), Calidris ruficollis MG736926 (Chen et al.…”
Section: Methodsmentioning
confidence: 99%
“…This monotypic treatment is probably due to the many particularities of this species, which distinguish ruffs from other Charadriiformes. However, recent phylogenetic studies based on nuclear and mitochondrial genes [14,15] revealed that the species was closely related to birds belonging to the genus Calidris MERREM 1804. Accordingly, Calidris pugnax is now acknowledged as the valid scientific name of the species [16][17][18].…”
Section: Systematics and Taxonomymentioning
confidence: 99%
“…This mon-otypic treatment is probably due to the many particularities of this species, which distinguish ruffs from other Charadriiformes. However, recent phylogenetic studies based on nuclear and mitochondrial genes [15,16] revealed that the species was closely related to birds belonging to the genus Calidris MERREM 1804. Accordingly, Calidris pugnax is now acknowledged as the valid scientific name of the species [17][18][19].…”
Section: Systematics and Taxonomymentioning
confidence: 99%